Drug Interaction Study of Antihypertension in Geriatric Patients Diagnosed Hypertension at Puskesmas Mauponggo, Nusa Tenggara Timur - Virginia, Dita Maria; Jago Uko, Maria Anjeline (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Hypertension is one of the main causes of mortality and morbidity in Indonesia. Treatment of hypertension in geriatric patients has the potential to increase the risk of drug-drug interactions because geriatric patients tend to experience polypharmacy. This study aims to analyze differences in mean blood pressure based on the interaction of antihypertensive drugs with other therapies in geriatric patients who suffer from hypertension at the Mauponggo Health Center, Nagekeo, East Nusa Tenggara. This research is a type of analytic observational research using a research design cross sectional. Data collection was carried out retrospectively. Data was collected using medical records collected from January to December 2021. In this study, a sample of 101 patients was obtained who met the predetermined inclusion and exclusion criteria. Data analysis using unpaired T test to analyze the difference of mean blood pressure based on the presence of antihypertensive drug interactions in geriatric patients, regarding on a significance level of p<0.05. The results showed that drug interactions had no effect on the mean systolic (p-value 0.063), or average diastolic (pvalue 0.392) in geriatric patients suffering from hypertension at the Mauponggo Health Center, Nagekeo, East Nusa Tenggara. Antihypertensive drug interactions did not affect the average blood pressure in geriatric patients in this study. Further research is required to classify the types of antihypertensive drugs that significantly impact blood pressure.